STUDENT PERSPECTIVE IN TRANSLATING DESCRIPTIVE AND NARRATIVE TEXT FROM ENGLISH TO INDONESIA AT SMAN 1 GEBANG - Nadila Yusrianti; Sondang Manik; Erika Sinambela (Merwin Publisher, 2026)
Translation plays an important role in English language learning, particularly at the high school level in Indonesia, where students are often tasked with translating descriptive and narrative texts. The purpose of this study is to analyze students' perspectives in translating descriptive and narrative texts from English to Indonesian at SMAN 1 Gebang. The research method used in this study is qualitative by using a questionnaire as a data collection tool to see students' perspectives in translating descriptive and narrative texts using a Likert scale to measure students' perspectives in translating. The location of the study was conducted at SMAN 1 Gebang using a sample of 20 students selected through random sampling. The findings showed that 50% of students often had difficulty in understanding vocabulary, maintaining the original meaning of the text, and reformulating sentences in Indonesian. Some 40% of students relied heavily on context and tools such as dictionaries or online translators due to lack of mastery of vocabulary and understanding of translation strategies. In addition, 40% of students experienced cultural and linguistic differences between English and Indonesian identified as the main factors affecting translation results.